Pelatihan Keterampilan Melalui Diversifikasi Produk Olahan Makanan Berbasis Ikan Bagi Kelompok Wanita Adipura Rt 04/RW 04 Kelurahan Lere Kecamatan Palu Barat - Hasmari Noer; If'all If'all; Arfan Arfan; Juhana Juhana (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Today's urban communities tend to buy practical food, namely those that are ready to cook (ready to be cooked) and ready to eat (ready to eat). Ready of cook means that it takes less time to prepare food. One form of food that is ready to cook is processed fish-based food. Partner problems are: Can fish-based food processing diversification be a business opportunity; and can increase public interest in consuming fish. Adipura Women's Group RT 04/RW 04 Lere Village, West Palu District, which is incorporated is still very limited in knowledge about diversification of fish-based food processing. The purpose of the activity is to find out business opportunities for diversifying fish-based food processing. To find out the public's interest in fish-based food processing. Improving the skills of the Adipura Women's group RT 04/RW 04 Lere Village, West Palu District in diversifying fish-based food processing. Using the Community Education method with Participatory Rural Appraisal (PRA/RRA), training methods, trial demonstrations, and coaching and evaluation of partner small business groups. The methods applied are: The methods applied to this activity in order to build human resources, especially group partners through the stages of implementing the activities, are field surveys, socialization, training, discussions, demonstration plots and mentoring and monev. The result of this training activity is an increase in the ability to run a partner's business through the training activities held. Increasing the ability and income of the community partners in activities with the technology of processing fish into various types of processed products, is one of food diversification and food preservation.